DNases of Acholeplasma spp. - Roganti, F S (1983)
One strain from each of seven species of Acholeplasma was examined for the presence of DNases. Six of the strains were found to be DNase positive when assayed with DNA-methyl-green-containing agar, indicating that this method can be used to differentiate the seventh strain, Acholeplasma axanthum, from the remaining Acholeplasma spp. Electrophoretic patterns obtained from sodium dodecyl sulfate-polyacrylamide gels containing DNA revealed DNases in the cell extracts of all seven strains and in the supernatant growth medium of five of the strains. The electrophoretic patterns were highly characteristic for each strain and can be used for the rapid identification of different strains of Acholeplasma.